2021
DOI: 10.1021/acsabm.1c00218
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Photodynamic Action of Porphyrin, Chlorin, and Isobacteriochlorin Derivatives toward a Melanotic Cell Line

Abstract: Melanoma is the most dangerous form of skin cancer, with an abrupt growth of its incidence over the last years. It is extremely resistant to traditional treatments such as chemotherapy and radiotherapy, but therapies for this cancer are gaining attention. Photodynamic therapy (PDT) is considered an effective modality to treat several types of skin cancers and can offer the possibility to treat one of the most aggressive ones: melanoma. In this work, the effect of PDT on a melanotic cell line (B16F10 cells) was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 64 publications
2
12
0
Order By: Relevance
“…Naturally occurring chlorophylls and bacteriochlorophylls are essential constituents of plants and bacteria, often called the “pigments of life” [ 134 , 135 ] owing to their important role in photosynthetic processes. Nowadays, their synthetic counterparts also present multiple applications essentially due to their absorbance of light in a broad range of the spectrum, particularly in the red (chlorins) and near infra-red region, NIR (bacteriochlorins) [ 65 , 143 , 144 , 145 , 146 ]. Intense red and NIR photons absorption is a desirable feature for biomedical applications (Imaging, PDT, aPDT), since the phototherapeutic window (650–900 nm) for electromagnetic radiation is the most penetrating and least harmful to human tissues [ 147 , 148 ].…”
Section: Synthetic Access To Cellulose-based Photosensitizersmentioning
confidence: 99%
“…Naturally occurring chlorophylls and bacteriochlorophylls are essential constituents of plants and bacteria, often called the “pigments of life” [ 134 , 135 ] owing to their important role in photosynthetic processes. Nowadays, their synthetic counterparts also present multiple applications essentially due to their absorbance of light in a broad range of the spectrum, particularly in the red (chlorins) and near infra-red region, NIR (bacteriochlorins) [ 65 , 143 , 144 , 145 , 146 ]. Intense red and NIR photons absorption is a desirable feature for biomedical applications (Imaging, PDT, aPDT), since the phototherapeutic window (650–900 nm) for electromagnetic radiation is the most penetrating and least harmful to human tissues [ 147 , 148 ].…”
Section: Synthetic Access To Cellulose-based Photosensitizersmentioning
confidence: 99%
“…Considering that photodynamic therapy (PDT) can be an effective modality to treat several types of skin cancers, namely the most aggressive ones like melanoma, Castro et al 61 decided to revisit the reaction of 5,10,15-tris(pentafluorophenyl)-20-(4-pyridyl)porphyrin 52 with the azomethine ylide AZ1 and to evaluate the photodynamic action of the resulting chlorin 53 and isobacteriochlorin 54 (Figure 13) towards the melanotic cell line (B16F10). For comparison, the studies were also extended to the starting porphyrin 52.…”
Section: Figure 12mentioning
confidence: 99%
“…Castro et al . (27) synthesized chlorin derivatives using 1,3‐dipolar cycloadditions on 5,10,15‐tris(pentafluorophenyl)‐20‐(4‐pyridyl) porphyrin, resulting in enhanced singlet oxygen generation ( φ Δ values from 0.65 to 0.81) with good photostability and with relatively strong absorption band in 650 nm. The authors reported that the reduction of one of the β‐pyrrolic because of the introduction of a pyrrolidine group is responsible for the intense absorption in 650 nm.…”
Section: Photosensitizersmentioning
confidence: 99%
“…Chemical structures of Porphyrin derivatives. Summarized for references (27,41,42). [Colour figure can be viewed at wileyonlinelibrary.com]…”
Section: Photosensitizersmentioning
confidence: 99%